St. James Press gay & lesbian almanac - Schlager, Neil, 1966- (Detroit : St. James Press, 1998)
'This important reference work is one of the first to devote equal attention to both gay men and lesbians. Its objective approach encourages in-depth study of gay and lesbian history, culture, and experience in 20th-century America.. The book's 23 sections include a chronology, an annotated list of organizations, significant historical documents important to the gay and lesbian movement, and in-depth discussions of gay and lesbian involvement in such fields as politics, film, music, science, sports, travel, leisure, and visual and performing arts. Each section includes biographical profiles of prominent people in each field and extensive bibliographies of books. articles, and Web sites. The evenhanded approach to this subject makes this book an important purchase for all libraries'.--'Outstanding Reference Sources : the 1999 Selection of New Titles', American Libraries, May 1999. Comp. by the Reference Sources Committee, RUSA, ALA
Includes bibliographical references and index
Keywords: Homosexuality, Male -- United States -- History; Lesbianism -- United States -- History; Gay men -- United States -- Biography; Lesbians -- United States -- Biography; Gay men -- United States -- History; Lesbians -- United States -- History